ANALISIS PENENTUAN KOMODITAS UNGGULAN SEKTOR PERTANIAN DI KABUPATEN TOLITOLI - Ahdan, Ahdan (Katalogis, 2015)
Local governments should be able to prioritise the sub-sector and the preferred crop, prime and which is considered as a sub-sector basis to optimise the economic advantages in the region. Understanding the development planning priorities and commodity sub-sector of agricultural in Tolitoli Regency, then it is necessary to acknowledge which the prime subsector of agricultural sector and the main commodity of agricultural sector in Tolitoli Regency. The research was conducted in the period 2014 - 2015 by several methods of analysis: 1) Location Quotient, 2) Analytical Hierarchy Procces (AHP) 3) Exponential Comparative Method /MPE. The criteria used is based on 12 normative criteria of the Indonesian Ministry of Home Affair, Number 9, 2014. The results show that the plantation sub-sector is the only sector basis in the period 2009-2014 of the survey with the value of LQ=1,3694 or LQ>1. Similarly, the plantation subsector is nominated as the prime subsector in Tolitoli regency with weight priority value of 0,2927. In addition, the cloves commodity is the most popular commodity in Tolitoli Regency with the MPE total weight of 13,1416, and this commodity is nominated as commodity basis with the LQ value of 13,5754. It is understandable because this area has long been well known as cloves plantations.